2008
DOI: 10.1139/l07-092
|View full text |Cite
|
Sign up to set email alerts
|

Asphalt modification with used lubricating oil

Abstract: The viability of used lubricating oil as an asphalt modifier was studied, with the enhancement of the low-temperature grade as the specific goal. Used oil modification was found to improve the Superpave low-temperature performance grade (PG), but at the expense of the high-temperature PG grade. When evaluated according to the Superpave MP1 specification, the low-temperature grade of the modified asphalt was not significantly improved due to failure of the bending beam rheometer (BBR) test’s m value. When evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(28 citation statements)
references
References 4 publications
0
28
0
Order By: Relevance
“…The use of vacuum distilled residues from the re-refining of used motor oils as a blend stock in paving grade bitumen has occurred in isolated markets in North America for more than 30 years. Published information discussing the potential benefits of the product are more recent (Herrington, 1992) (Hayner, 1999) (Villanueva A., 2008). Within the last three years, the increasing need for low stiffness bitumen for use in bituminous mixtures with ever increasing amounts of RAP and RAS (Reclaimed Asphalt Shingles) has created a growing market for this low cost residual byproduct.…”
Section: Introductionmentioning
confidence: 99%
“…The use of vacuum distilled residues from the re-refining of used motor oils as a blend stock in paving grade bitumen has occurred in isolated markets in North America for more than 30 years. Published information discussing the potential benefits of the product are more recent (Herrington, 1992) (Hayner, 1999) (Villanueva A., 2008). Within the last three years, the increasing need for low stiffness bitumen for use in bituminous mixtures with ever increasing amounts of RAP and RAS (Reclaimed Asphalt Shingles) has created a growing market for this low cost residual byproduct.…”
Section: Introductionmentioning
confidence: 99%
“…The typical value of mixing was found to be around 160C due to the presence of the stiff aged binder. [30] The mixing temperature is 160C with 1 hour time of mixing and mixing speed 500 rpm. Borhan et al, [31] The mixing temperature, time of mixing and mixing speed was not stated.…”
Section: 31 Incorporating Waste Oil Into Pavement Materialsmentioning
confidence: 99%
“…They found that the addition of WEO is beneficial to prevent asphalt aging and improving fatigue performance, but WEO has a negative effect on the rutting resistance of asphalt. Villanueva et al [8] prepared the modified asphalt with used lubricating oil (or engine oil). They found that used lubricating oil improves the anti-cracking performance at low-temperatures and reduces the quality loss of asphalt after rolling thin film oven test (RTFOT).…”
Section: Introductionmentioning
confidence: 99%